A new method for the determination of naphatylamines in workplace air for occupational exposure assessment - Anna Jeżewska; Dorota Kondej; Agnieszka Woźnica (Medycyna Pracy, 2021)
Background Naphthylamine (NA), i.e., 1-naphthylamine (1-NA) and 2-naphthylamine (2-NA) and its salts (2-naphthylamine hydrochloride and 2-naphthylamine acetate) are colorless crystalline solids. They have been used, among others, in the production of paints and dyes. In the European Union, 1-NA is classified as a toxic substance, and 2-NA and its salts as carcinogenic category 1A. The aim of this study was to develop a new method for the determination of NA, which will enable the determination of 1-NA and 2-NA and its salts in the working environment, in the concentration range of 0.3–6 μg/m 3 .